Factors influencing purchase intentions through social networking websites among Malaysian students - Fard, Saeideh Sharifi (2017)
As in many other countries, social media has today become one of the fastest and strongest networking and communication tools in Malaysia. This has facilitated the growth of online marketing and online shopping in the country. Realizing this development, companies have to venture into the world of social media. Identifying the factors influencing consumer online purchase intentions through social networking sites (SNSs) is essential in advancing online shopping via SNSs. This study explores the integration of trust into the extended unified theory of acceptance and use of technology (UTAUT2) in an attempt to investigate how the proposed model provides better explanation of the factors affecting purchase intention in the use of SNSs. To achieve the purpose of the study, a cross sectional survey using a self-administered questionnaire was carried to test the hypothesized model. Using a cluster sampling method, a total of 370 undergraduate and graduate students from four universities in in Malaysia participated in the survey. Results of the descriptive analysis showed that (1) the level of online purchase intention was moderate to high, (2) the levels of performance expectancy and perceived ad informativeness were high, (3) the levels of effort expectancy, hedonic motivation, and habit were moderate, and (4) the level of social influence was low to moderate among students surveyed. Results of structural equation modeling analysis showed that the proposed model is relatively appropriate to explain the online consumer behavior (x2/df = 1.73, p < .005, CFI = .943; IFI = .943, TLI = .936, RMSEA = .045). The results showed that performance expectancy, hedonic motivation, habit, and perceived ad informativeness positively affect consumer’s intentions to use SNSs. However, effort expectancy and social influence factors do not influence consumer intention to use SNSs. Results of the Multi-group analysis of the moderating effect of trust on the relationships of the selected factors with purchase intention through SNSs revealed that trust in SNSs is a significant moderator when explaining online consumer behavior. The results of the study revealed that selected UTAUT2 constructs plus perceived ad informativeness has been found to explaining 0.60% variance in the direct model. In addition 63% and 54% of purchase intention through SNS variances are explained by moderation models, respectively. Recommendations for practice from the findings of the study are offered. Online marketers and online advertisers must consider online shopper behavior in designing successful online marketing via SNSs.